Express (3 + 13x - 6x^2)/(2x-3) in the form Ax + B + C/(2x - 3)

The answer is -3x + 2 + 9/(2x-3). That is A = -3, B = 2 and C = 9.

I will use the whiteboard during my interview to explain the working.

Answered by Sam M. Maths tutor

4710 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Given two functions x = at^3 and y = 4a, find dy/dx


Find the gradient of y=x^2-6x-16 at the point where the curve crosses the x-axis


Differentiate the function y = cos(sin(2x))?


Differentiate the expression x^6+5x^4+3 with respect to x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences